Perkembangan Motorik Halus Anak Usia 2-3 Tahun Melalui Bermain Sambil Belajar Di Posyandu (Bermadu) Desa Ciparay - Risdayah, Enok; Zulfa, Mayuha; Balqiyah, Nur Halizah; Hidayat, Taofik (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Fine motor skills are an important aspect of the development of children aged 2–3 years. Appropriate stimulation is needed to develop fine motor skills optimally. Playing while learning is an effective approach to motivating children's motoric, cognitive, and social development. Ciparay Village Posyandu plays a role in stimulating children's development. Group 56 KKN UIN Bandung implemented a play-while-learning program at Posyandu to stimulate the development of children's fine motor skills. This program includes various play activities that train children's hand and finger skills. Qualitative research was conducted to evaluate the effectiveness of the program and the factors that influence children's fine motor development. Playing while learning can stimulate fine motor development. However, not all children show maximum development, which is influenced by environmental factors and parental involvement. The findings are used to recommend improving the stimulation program at Posyandu. The play-while-learning program has been proven to be effective in stimulating fine motor skills. Parental participation needs to be increased. This research is useful for improving Posyandu services in supporting children's growth and development.